Project management in practice - Meredith, Jack R.; Shafer, Scott M. (Hoboken: John Wiley & son, 2021)
"The use of projects and project management continues to accelerate in our global societies. With the addition of Agile, project management is now also being used for dynamic, "quasi" projects: initiatives where the scope, budget, and deadline are changing constantly. One of the more interesting"--
Revised edition of the authors' Project management in practice, [2017]
Includes index.
Keywords: Project management